Investigating the influence of transition metal oxides on temperature dependent optical properties of PbCl2-TeO2 glasses for their evaluation as transparent large band gap semiconductors - Gedikoglu, N.; Ersundu, M. Celikbilek; Kostka, P.; Basinova, N.; Ersundu, A. E. (ELSEVIER SCIENCE SA, 2018)
A series of ternary glasses in the MeO-PbCl2-TeO2 (MeO = Bi2O3, MoO3, Sb2O3, WO3, ZnO) system have been synthesized by conventional melt quenching technique. Thermal properties of glasses - glass transition (T-g) and crystallization (T-c/T-p) temperatures, temperature difference (Delta T) and thermal stability (S) values - were determined using differential scanning calorimetry. The influence of transition metal oxides on refractive index, position and shift rate of absorption edge, optical band gap energy (E-opt) and Urbach energy (Delta E) was investigated and their dependence on temperature was studied. The Eopt and DE values of all glasses studied in this work were found to be comparable with the values corresponding to some semiconductors. The glasses under study show great potential for applications in optoelectronics. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Tellurite glasses; Transition metal oxides; Temperature dependent optical properties; Optical band gap; DOPED TELLURITE GLASSES; TEO2-PBCL2 GLASSES; DC CONDUCTIVITY; SYSTEM; SPECTRA; BEHAVIOR; Chemistry; Materials Science; Metallurgy & Metallurgical Engineering